(untitled) (Journal of School Administration Research and Development, 2022)
Understanding the current and preferred organizational culture among school teachers in India is a primary requirement, particularly when the National Educational Policy (NEP) is being implemented. Measuring the competing values using the Organizational Culture Assessment Instrument (OCAI) provides information about the dominant characteristics of the organizational culture and the school teachers’ preferences. We surveyed school teachers and received 273 responses. Research revealed that clan culture is the overall current and preferred organizational culture type. Many of the results are not a surprise. However, we found that organizational leadership is currently in the hierarchy culture and strategic emphasis is on adhocracy, whereas teachers prefer a clan culture on these dimensions. Teachers expect school leaders to be the ones who facilitate the path to achieve, provide mentoring, and are instrumental in team building. They prefer a culture that provides for the development of human capital, promotes high trust and transparency among teachers, and offers an opportunity to participate in decision-making. This study is unique as it measures schools’ organizational culture that has not been done earlier in the Indian context. The results suggest implications on the leadership practices and the strategic emphasis that need to change, in order to facilitate the implementation of the National Education Policy (NEP).